Contrasting effects of fresh and fermented kimchi consumption on gut microbiota composition and gene expression related to metabolic syndrome in obese Korean women. Issue 5 (23rd March 2015) - Han, Kyungsun; Bose, Shambhunath; Wang, Jing‐hua; Kim, Bong‐Soo; Kim, Mi Jeong; Kim, Eun‐Jung; Kim, Hojun
<x xml:space="preserve">Abstract</x> Accumulating evidence suggests relationship of compositional changes of gut microbiota with onset of metabolic disorders and obesity. Kimchi, a traditional Korean side dish, is known for its beneficial impact on metabolic parameters and anti‐obesity effects. The current study was designed to evaluate the association between gut microbiota and human genome after kimchi intervention in an effort to understand the molecular mechanism(s) underlying the antiobesity impact of kimchi. Twenty‐four obese women were randomly assigned to either fresh or fermented kimchi group for eight weeks of kimchi intervention. Pyrosequencing of fecal microbiota and microarray analyses of blood samples revealed that fresh and fermented kimchi interventions exerted differential effects on the obesity‐related clinical parameters. Correlations of these effects with changes in blood gene expression and gut microbial population were more evident in the fermented kimchi group than the fresh kimchi group.